2020
DOI: 10.5194/acp-2020-308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the role of trend and variability of hydroxyl radical (OH) in the global methane budget

Abstract: Abstract. Decadal trends and interannual variations in the hydroxyl radical (OH), while poorly constrained at present, are critical for understanding the observed evolution of atmospheric methane (CH4). Through analyzing the OH fields simulated by the model ensemble of the Chemistry–Climate Model Initiative (CCMI), we find (1) the negative OH anomalies during the El Niño years mainly corresponding to the enhanced carbon monoxide (CO) emissions from biomass burning and (2) a positive OH trend during 1980–2010 d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The ENSO signal is weak during the early 2000s, resulting in small interannual variations of tropospheric OH burden (Zhao et al, 2019). The mechanisms of OH variations related to ENSO and their impacts on the CH 4 budget need to be explored by inversions, but over a longer time period than this study (e.g., 1980-2010Zhao et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The ENSO signal is weak during the early 2000s, resulting in small interannual variations of tropospheric OH burden (Zhao et al, 2019). The mechanisms of OH variations related to ENSO and their impacts on the CH 4 budget need to be explored by inversions, but over a longer time period than this study (e.g., 1980-2010Zhao et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…One way can be to build semi-empirical OH fields by combining atmospheric chemistry models, observation-based meteorological data, and chemical species concentrations (e.g., NO x , CO, VOCs, etc.) as initiated in Spivakovsky et al (2000); another way is conducting a multispecies variational inversion of OH (e.g., Zheng et al, 2019) with hydrofluorocarbon (HFC) species (Liang et al, 2017), formaldehyde (Wolfe et al, 2019), CH 4 (Zhang et al, 2018;Maasakkers et al, 2019), or CO (Zheng et al, 2019). In addition, as suggested by Prather et al (2017), OH inversion would benefit from including in the prior data the responses of [OH] to variations of the precursor emissions (e.g., biomass burning and lighting) using the uncertainties estimated by 3D models.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There are many proposed reasons for this "missing" reactivity, such as short-lived VOCs that were not measured (Kovacs et al, 2003) or in the rainforests some mixture of unidentified biogenic emissions and photooxidation products (Edwards et al, 2013;Nölscher et al, 2016). An improved understanding of OH temporal variation is vital to understanding key aspects of atmospheric chemistry, such as interannual to decadal variability in methane (Turner et al, 2019;Zhao et al, 2020). Studies using MCF observations in combination with box-model analyses show similar annual OH anomalies between 1995 and 2010, with a broadly negative anomaly of -6 to 0 % between 1995 and 1999, a positive anomaly of 0 to 6 % between 1999 and 2007 and a negative anomaly of -5 to 0 % between 2007 and 2010 (Montzka et al, 2011;Rigby et al, 2017;Turner et al, 2017;Patra et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…He et al, (2020) found negative anomalies of -5 to 0 % between 1995 and 2005 and then positive anomalies of 0 to 4 % between 2005 and 2017. A study by Zhao et al, (2020) found a multi-model mean increase of 0.7 ×10 5 molecule cm -3 between 1980 and 2010, equivalent to around 0.1-0.5 % yr -1 , with the greatest rate of increase in the final decade (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010). The OH increase from 2000-2010 was predominantly due to that in the primary production term (O( 1 D) + H2O) though also to a decrease in the CO sink term (OH + CO).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, we can hypothesize. For example, El Niño years (high MEI) are associated with more wildfires, resulting in higher CO emissions which could suppress OH concentrations (Zhao et al, 2020;Nguyen et al, 2020). La Niña years (low MEI) are associated with increased convection over the Pacific, increased lightning NO x production and by extent increased OH recycling (Turner et al, 2018 regionally (Oman et al, 2011).…”
Section: That Variability In [Oh]mentioning
confidence: 99%